If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (-4x + 5) = 12 Reorder the terms: 4x + (5 + -4x) = 12 Remove parenthesis around (5 + -4x) 4x + 5 + -4x = 12 Reorder the terms: 5 + 4x + -4x = 12 Combine like terms: 4x + -4x = 0 5 + 0 = 12 5 = 12 Solving 5 = 12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (x+1)(x-3)(x^2-6x+18)=equation | | 0.30=log(1/x) | | 1/3x4/3= | | ln(7k-3)=2 | | 0.30=log(1/T) | | 0.25(d+56)=55 | | -8x-3(-4x-6)=10 | | (4+3n)+(5+4d)= | | -8-b+4b-2-3b= | | -8-3p=8(1+8p) | | (x+1)(x-3)(x-6x+18)=equation | | 2x+10=90-(4x+20) | | (-4,11);m=3/4 | | 768=4(x+18) | | 0.25(d+56)=64 | | 2x^2+7=12 | | 3x^4+18=21x | | 7x+-13=6x+-17 | | 15-3k=10(k-5) | | (2m)3/5 | | 90=33 | | 6(r-4)+r+30-7r=p | | 1,134=6(x+16) | | 1x+4x+6x= | | 4x-2=1/3x | | (5n-6)(n+4)=0 | | -4x-3(2-7x)= | | z+4(2e+3)=15 | | 3(y-2)=15p+60 | | 2x-832x/9 | | (x+1)(x-3)(x-3+3i)(x-3-3i)=equation | | -log(x-5)+log(x+5)=2 |